Micropatterning of bioactive glass nanoparticles on chitosan membranes for spatial controlled biomineralization - Luz, Gisela (2012)
Bioactive glass nanoparticles (BG-NPs) capable of inducing apatite precipitation upon immersion in simulated body fluid (SBF) were patterned on free-standing chitosan membranes by microcontact printing using a poly(dimethylsiloxane) (PDMS) stamp inked in a BG-NPs pad. Formation of the patterns was characterized by scanning electron microscopy (SEM). Mineralization of the bioactive glass patterns was induced in vitro by soaking the samples in SBF over different time points up to 7 days. The confined apatite deposition in the patterned regions with diameters of 50 μm was confirmed by Fourier-transformed infrared spectroscopy (FTIR), energy-dispersive X-ray (EDX) analysis, and SEM. In vitro tests confirmed the preferential attachment and proliferation of L929 cells to the areas printed with BG-NPs of the membranes. This approach permits one to spatially control the properties of biomaterials at the microlevel and could be potentially used in guided tissue regeneration for skin, vascular, articular, and bone tissue engineering and in cellular cocultures or to develop substrates able to confine cells in regions with controlled geometry at the cell’s length scale.